Firm Heterogeneity and Imperfect Competition in Global Production Networks - Hanwei Huang; Kalina Manova; Oscar Perelló; Frank Pisch; Kalina B. Manova (CESifo GmbH, 2024)
We study the role of firm heterogeneity and imperfect competition for global production networks and the gains from trade. We develop a quantifiable trade model with two-sided firm heterogeneity, matching frictions, and oligopolistic competition upstream. More productive buyers endogenously match with more suppliers, thereby inducing tougher competition among them to enjoy lower input costs and superior performance. Transaction-level customs data confirms that downstream French and Chilean firms import higher values and quantities at lower prices as upstream Chinese markets become more competitive over time, with stronger responses by larger firms. Moreover, suppliers charge more diversified buyers lower mark-ups. Counterfactual analysis indicates that entry upstream benefits high-productivity buyers, while lower matching or trade costs benefit all buyers, with the biggest boost to mid-productivity buyers. All three shocks generate sizeable welfare gains, especially under package reforms. Global production networks thus mediate bigger effects and cross-border spillovers from industrial and trade policies.
Keywords: D24; F10; F12; F14; L11; L22; 330; production networks; global value chains; matching frictions; imperfect competition; gains from trade